Return on equity factors - V. B. Frolova (Путеводитель предпринимателя, 2020)
The article contains the results of research into the formation of a financial strategy for integrated holding structures in the field of information and communication, in particular, publishing organizations, as well as the factor model developed by the author, which allows assessing the impact of tax optimization results on the return on equity.